COMPARATIVE STUDIES OF SOIL NUTRIENT STATUS AND FRUIT CHARACTERISTICS OF LITCHI (LITCHI CHINENSIS. SONN) ORCHARD UNDER SUB-MOUTANE ZONE OF PUNJAB - SARVPRIYA SINGH; NAV PREM SINGH; DHANWINDER SINGH; RUQIYAMAJEED (The Bioscan, 2015)
An experiment was conducted during 2013 and 2014 to study the soil nutrient status and fruit characteristics of Litchi (Litchi chinensis Sonn.) orchards under Sub-mountane zone of Punjab. Available soil pH (6.7 to 8.6), EC (0.15-0.44) dS/m, OC (0.22-0.39%), CaCO3 (0.11-4.90%), N (302.4-436.8 kg/ha), P(11.9 to 24.3 kg/ha) and K (70.0 to 373.0 kg/ha) whereas soil micronutrients ranged from Zn(0.3-10.6 mg/ha), Fe(2.25-105.6 mg/ha), Mn(0.18-18.8 mg/ha) and Cu(-0.4-8-8.8) at 0-30 cm depth of soil in both litchi cultivars. Soil N, K and Zn content was positive and statistically significant with fruit yield whereas soil K was also positively significant correlate with fruit size, pulp and TSS and pulp stone ratio. From the present investigation it was conclude that subsurface of soil was deficient in soil N and k however the surface soil was adequate but few orchards were inadequate range.Soil micro-nutrients Zn,Cu,Mn and Fe content of soil were available in adequate ranges however fewer samples of Zn and Fe available in lower percentage as compare to other micro-nutrients.